A Comparative Study on Characterization of 12-Tungstophosphoric Acid Cesium Salt Depending on Synthesis Methods - Odes Akbay, Elif; Demir, Gulberk (Asian Journal of Chemistry, 2014)
12-Tungstophosphoric acid cesium salt, Cs2.5H0.5PW12O40, exhibits high catalytic activity for various kinds of acid-catalyzed reactions. This excellent catalytic effect of Cs2.5H0.5PW12O40 is attributed to its strong acidity, hydrophobicity, unique pore structure, etc. In this study, the methods published in the literature were modified by monitoring the aging, atmospheric drying-vacuum drying and calcination, addition rate of Cs2CO3 solution to 12-tungstophosphoric acid solution to enhance the surface properties of Cs-12-tungstophosphoric acid such as the surface area and porosity. The characteristic of the synthesized Cs-12-tungstophosphoric acid were obtained by the XRD, FTIR, SEM, TG-DTG, particle distribution and crystallite size and the results were compared with the finding in literature. The each modified methods have different effect on the BET surface area and porosity. The sample coded by 01G50V showed the highest surface area with 4.5 nm pore diameteramong synthesized 12-tungstophosphoric acid cesium salt.